IMPROVING STUDENTS’ SPEAKING SKILL AND INTEREST THROUGH DUOLINGO AS GAMIFICATION APPLICATION - Nina Nursuhaniah; Ruminda; Juhana (Indonesian Journal of Learning and Instruction, 2025)
Abstract: This experimental method focused on the effectiveness of Duolingo as a gamification application strategy to improve students’ speaking skills and interest, and to confirm the correlation between them. The participants were the tenth graders of SMAN 1 Mande selected randomly to be the experimental and control classes. The instruments were the pre-post speaking skill test and the pre-post speaking interest questionnaire. The analysis revealed that the significant score (2-tailed) or (P) of the post-speaking skill test obtained by both experimental and control classes was 0.00. Thus, the significant difference was confirmed. The quality of the experimental class on speaking skills was higher than that of the control class. It was decided that Duolingo, as a gamification application strategy, had an effective impact on improving speaking skills. Moreover, all significant scores (2-tailed) or (P) of the post-speaking interest questionnaire obtained by both experimental and control classes were 0.00. Thus, the significant difference was confirmed. The quality of the experimental class on speaking interest was higher than the control class. It exposed that Duolingo, as a gamification application strategy, had an effective impact on improving speaking interest. The experimental class achieved a mean score of 88.47, whereas the control class obtained a mean score of 79.17. The experimental class achieved a mean post-speaking interest score of 123.75, whereas the control class scored 99.69. Whereas, correlation coefficient was 0.007. Moreover, the significance score between speaking interest and speaking skill in the experimental class was 0.963, which was more than 0.05. Therefore, it implied that students’ speaking skills did not correlate significantly with their speaking interest. It could be concluded that Duolingo, as gamification, was quite effective in improving students’ speaking skills and speaking interest, but there was no correlation between speaking skills and speaking interest Keywords: Duolingo; gamification; speaking skill; speaking interest.